Family Supportive Leadership and Counterproductive Work Behavior: The Roles of Work-Family Conflict, Moral Disengagement and Personal Life Attribution - Jin, Shan; Zhu, Xiji; Fu, Xiaoxia; Wang, Jian (Frontiers in Psychology, 2022)
Counterproductive work behavior (CWB) is one of the most common behavioral decisions of employees in the workplace that negatively impacts the sustainable development of enterprises. Previous studies have shown that individuals make counterproductive behavior decisions for different reasons. Some individuals engage in counterproductive work behavior due to cognitive factors (i.e., perceived organizational justice and psychological contract breakdown), whereas others engage in counterproductive work behaviors in response to leadership behaviors (i.e., abusive management). The conservation of resources (COR) theory holds that individuals have the tendency to preserve, protect and acquire resources. When experiencing the loss of resources, individuals will show irrational and aggressive behaviors in order to regain resources. When obtaining resources, individuals' tension and pressure will be relieved. To maintain or continue obtaining resources, individuals will show more positive work attitudes and behaviors.Therefore, using the COR theory as the main theoretical framework, this study explores a serial mediation model between family supportive leadership and counterproductive work behavior through work-family conflict and moral disengagement, moderated by personal life attribution. A three-wave survey of 251 medical workers from three hospitals found that family supportive leadership can reduce employees’ perceived work-family conflict, which leads to less moral disengagement, resulting in lower CWB. Personal life attribution strengthens the negative indirect effect of family supportive leadership on CWB by reinforcing the negative association between family supportive leadership and work-family conflict. This study uses the COR theory to explore the mechanism and boundary conditions of family supportive leadership and counterproductive work behavior from the perspective of negative work-family relationship, which enriches the research content of existing theories. Moreover, this study has important guiding significance for managers to take effective measures to reduce counterproductive work behavior.